`In the Short Run Blasé, in the Long Run Risqué'. On the Effects of Monetary Policy on Bank Credit Risk-Taking in the Short versus Long Run - Gabriel Jiménez; Steven Ongena; José-Luis Peydró; Jesús Saurina (Schmalenbach Business Review, 2017)
We identify the impact of short-term interest rates on credit risk-taking in the short and long run by analyzing a comprehensive credit register from Spain, a country where for the last twenty years monetary policy was mostly decided abroad. Duration analyses show that lower overnight rates prior to loan origination lead banks to lend more to borrowers with a worse credit history and to grant more loans with a higher per-period probability of default. Lower overnight rates during the life of the loan reduce this probability. Bank, borrower and market characteristics determine the impact of overnight rates on credit risk-taking.
Keywords: E44; E5; G21; 330; monetary policy; low interest rates; financial stability; lending standards; credit risk-taking; credit composition; business cycle; liquidity risk